2014
DOI: 10.3389/fncel.2014.00104
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytic receptors activate and immune inhibitory receptor SIRPα inhibits phagocytosis through paxillin and cofilin

Abstract: The innate immune function of phagocytosis of apoptotic cells, tissue debris, pathogens, and cancer cells is essential for homeostasis, tissue repair, fighting infection, and combating malignancy. Phagocytosis is carried out in the central nervous system (CNS) by resident microglia and in both CNS and peripheral nervous system by recruited macrophages. While phagocytosis proceeds, bystander healthy cells protect themselves by sending a “do not eat me” message to phagocytes as CD47 on their surface ligates immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 30 publications
5
39
1
Order By: Relevance
“…To understand how the activation of p38MAPK affects resting microglia functions, paxillin phosphorylation was examined since paxillin has been reported to be a major substrate for p38MAPK and ERK1/2 at Ser 83 residue ( Huang et al, 2004 ). Paxillin, a focal adhesion adaptor protein, is known to be involved in focal adhesion dynamics, cell migration, and phagocytosis ( Tsubouchi et al, 2002 ; Webb et al, 2004 ; Gitik et al, 2014 ). Studies have shown that paxillin interacts with many proteins and these interactions result in changes in the organization of the actin cytoskeleton, which are necessary for controlling phagocytosis and cell motility ( Turner, 2000 ; Duran et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…To understand how the activation of p38MAPK affects resting microglia functions, paxillin phosphorylation was examined since paxillin has been reported to be a major substrate for p38MAPK and ERK1/2 at Ser 83 residue ( Huang et al, 2004 ). Paxillin, a focal adhesion adaptor protein, is known to be involved in focal adhesion dynamics, cell migration, and phagocytosis ( Tsubouchi et al, 2002 ; Webb et al, 2004 ; Gitik et al, 2014 ). Studies have shown that paxillin interacts with many proteins and these interactions result in changes in the organization of the actin cytoskeleton, which are necessary for controlling phagocytosis and cell motility ( Turner, 2000 ; Duran et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…M1/2 microglia activation was not studied previously in the context of chronic morphine administration. We defined M2 microglia according to high expression of CD172a (SIRPa), which has been shown to prevent phagocytosis and to exert anti-inflammatory properties when paired with CD47 (Latour et al, 2001;Barclay and Van den Berg, 2014;Gitik et al, 2014). It should be stated, however, that the concept of M1 and M2 polarization may over-simplify the broad spectrum of microglial activation phenotypes, but also that heterogeneity of microglial populations is not only limited to M1/2 phenotypes (Cherry et al, 2014;Chen and Trapp, 2016;Ransohoff, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, up-regulation of AC and pyridoxal-5′-phosphate phosphatase/chronophin mediate astroglial apoptosis after status epilepticus [26]. In activated microglia, cofilin is involved in the regulation of NADPH oxidase activity [27] and phagocytosis [28,29]. Accordingly, future studies are warranted to elucidate the role of cofilin in microglial activation and astrocytes during ischemia.…”
Section: Discussionmentioning
confidence: 99%